Gaze behavior of trampoline gymnasts during a back tuck somersault - Natrup, J.; Bramme, J.; de Lussanet, M. H. E.; Boström, K. J.; Lappe, M.; Wagner, H. (Human Movement Science, 2020)
In trampolining, gymnasts perform a variety of rotational jumping elements and have to demonstrate perfect control of the body during the flying phase. The performance of a somersault should include an opening phase, i.e. the legs are fully extended pointing vertically at 180° called "kick-out". As previous studies have shown, gaze behavior is essential for the controlling during the flight phase and to prepare for a perfect landing. Gymnasts supposedly use the trampoline bed as orientation and differences in gaze behavior can be expected, depending on how a somersault is performed. The present study investigates the gaze behavior of gymnasts during a back tuck somersault on the trampoline. Eleven experienced trampoline gymnasts performed back tuck somersaults with and without a kick-out while wearing a light weight portable eye-tracking device. All subjects fixated their gaze on a specific point at the trampoline bed and thus used visual information to prepare for landing. During the period of fixation, gymnasts' eyes moved continuously downwards to counteract the backwards head movement. The point of fixation differed between each somersault. Apparently, the fixation position depended on the gymnast's landing position in the bed. Performing a somersault with a kick-out allows gymnasts to orient themselves earlier and thus prepare sooner for landing. Unexpectedly, gymnasts of a higher performance class fixated the bed later compared to less experienced athletes. Supposedly, gymnasts of a better class can allow themselves to fixate later in order to optimize the form and execution of a somersault.